Two new polyketides from Nocardiopsis lucentensis DSM 44048. Issue 9 (2nd May 2016) - Sun, Ming-Wei; Guo, Zhi-Xing; Lu, Chun-Hua
Abstract: Two new polyketides, namely lucentides A (1 ) and B (2 ), together with 19-hydroxyprotylonolide (3 ) were isolated from Nocardiopsis lucentensis DSM 44048. Their structures were elucidated by analysis of their high-resolution mass spectrometry (HR-MS) and 1D, 2D nuclear magnetic resonance (NMR) spectroscopic data. The antibacterial activities of compounds1 –3 were evaluated. Graphical abstract: